Strategi Komunikasi Pemasaran Terpadu (IMC) Discovery Kartika Plaza Hotel Bali dalam Membangun Citra Perusahaan - Nugroho Setiawan, Thalia Patricia; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium, 2023)
Discovery Kartika Plaza Hotel is the oldest 5-star hotel in Bali's Kuta Beach area. Despite the pandemic, it still attracts tourists because of its corporate image of being a "Hotel Vintage yang Modern." This study examines the integrated marketing communication (IMC) strategy used by the hotel to establish this image. The concept used in this study is Integrated Marketing Communication (IMC) using a qualitative descriptive method with a post-positivism paradigm. Data collection techniques were carried out using semi-structured interviews, non-participant observation and document studies. Findings show that Discovery Kartika Plaza Hotel Bali implements the marketing mix concept, encompassing product, price, place, and promotion. Their promotional mix combines advertising, internet marketing, public relations, sales promotion, direct marketing, events and experiences, word-of-mout and personal selling. However, the integrated marketing communication strategy that has been carried out by DKPH Bali has not been able to describe the image as a “Hotel Vintage yang Modern” because it contains more cultural elements than the “vintage” itself. Keywords: Integrated Marketing Communication (IMC), Marketing Mix, Promotional Mix, Corporate Image